Crisis Vision : Race and the Cultural Production of Surveillance - Monahan, Torin (Book collections on Project MUSE., 2022)
"In Crisis Vision, Torin Monahan uses critical arts projects as an entry point to investigate the racializing effects of contemporary surveillance. The book explores the surveillance vocabularies such artworks generate, the subjectivities and relationships they represent and catalyze, their assumptions and omissions, and their participation in the cultural production of surveillance as a social category. Monahan develops the concept of "crisis vision" to describe a pervasive, destructive way of seeing that amplifies differences among individuals and inspires the scapegoating of those marked as Other. Monahan turns to artwork that engages with opacity, an aesthetic intervention that interferes with crisis vision by rejecting authorized regimes of visibility. These artworks, including Kai Wiedenhöfer's WALLonWALL project, Dries Depoorter's Jaywalking project, and Dread Scott's installation Stop, challenge viewers to question their own place within inherently unjust social orders-emphasizing ethical relations between strangers and thereby disrupting crisis vision"--